2020
DOI: 10.3390/su12229777
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Scientists Showed a Four-Fold Increase of Lynx Numbers in Lithuania

Abstract: By the early 2000s, Eurasian lynx (Lynx lynx) were nearly extirpated in Lithuania. To determine their status, we used snow-track counts in 2006–2012 and volunteer monitoring in 1999–2005 and 2015–2018. Using simple questionnaires, we collected incidental observations from hunters, foresters, and other interested citizens to estimate lynx distribution, abundance and extent of breeding. Citizen scientists provided 206 reports of 278 individual lynx that suggested expanding lynx distributions in central, western,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The Eurasian lynx (Lynx lynx) is the only wild member of the felids in Lithuania [9]. However, this species is not abundant and there were approximately 160 lynx individuals in Lithuania in 2018 [20]. Thus, the high prevalence of S. bovifelis implies that it is not solely felids that contribute to the spread of this species.…”
Section: Introductionmentioning
confidence: 99%
“…The Eurasian lynx (Lynx lynx) is the only wild member of the felids in Lithuania [9]. However, this species is not abundant and there were approximately 160 lynx individuals in Lithuania in 2018 [20]. Thus, the high prevalence of S. bovifelis implies that it is not solely felids that contribute to the spread of this species.…”
Section: Introductionmentioning
confidence: 99%
“…For Lithuania, we considered the possibility of direct counts by hunters and citizen scientists, but such counts would require intensive concerted action by many hunting clubs in order to obtain non-biased and robust number estimation, as observations should be done at the same time to avoid data overlapping. Our experience of using hunters for large carnivore monitoring showed that coverage of the entire country’s territory was not possible even for key species such as the wolf and lynx [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the Editorial is to introduce the Special Issue, "Mammal Status: Diversity, Abundance and Dynamics", which includes six papers from Europe [1][2][3][4][5][6], three of these representing Baltic countries [4][5][6], two papers from Asia [7,8] and one from South America [9]. Four papers deal with carnivores (the snow leopard, gray wolf, Eurasian lynx, and Eurasian otter), two with ungulates (moose and Andean tapir), two with small mammals (including the endangered European ground squirrel), and one with the wide mammal complex, including many small and medium carnivores in Indonesia.…”
mentioning
confidence: 99%
“…Two other papers in the book relate to carnivore species no longer significantly endangered, at least on the European scale [1,5]. In Italy, an analysis of the Eurasian otter (Lutra lutra) living at the northernmost limit of its range, suggested that the current population is larger than the minimum viable population size [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation